Indonesia Pengembangan Website dan Promosi Pemasaran Chlorella Jelly Genki Di Kecamatan Tampan Kota Pekanbaru - Tengku Dahril; Deni Efizon; Efawani Efawani (Unri Conference Series: Community Engagement, 2021)
Chlorella Jelly Genki is a kind of health drink to increase the immune system or the level of people's immunity from various diseases including Covid-19 which is packaged in plastic cups that can be sold commercially at a price of Rp. 10,000/cup. Within 10 months from September 2020 to July 2021, 5321 cups have been sold with consumers from various circles including academics from universities such as students and lecturers at the Riau University and Riau Islamic University, Government Employees, Members of the Riau Regional House of Representatives, and the congregation of mosques such as the Rodatul Jannah mosque, Pekanbaru and the general public. To further increase the marketing reach of Chlorella Jelly Genki to the wider community, various strategies or efforts are needed, including developing websites using digital technology and marketing promotions through community service activities by involving student groups as the driving force through integrated Community Service Activities. Abdimas in 2021. This Community Service activity has been carried out from May 2021 to early August 2021, the report of which is presented in this paper. The first way is by developing a digital technology website and marketing promotion through social media in the form of a home page, which can be done under the name: http://genkinusantara.com/. While the second way is to directly invite the target community group to come to the Algae Research Center. The results of this community service show that of the 244 people who were invited, 115 people or 47.1% of them expressed their willingness to become a distributor or selling agent of Chlorella Jelly Genki. While 26 people (10.7%) were still unsure or still needed further consideration to become a distributor or sales agent, 94 people (38.5%) firmly stated that they were not or not yet willing and 94 people (38.5%) ) people (3.7%) did not provide an answer. All participants who attended stated that Chlorella Jelly Genki was delicious and very suitable to be developed in Riau and also in Indonesia.